The Effect of Local Government Revenue (PAD), Special Allocation Funds (DAK), Revenue Sharing Funds (DBH), and General Allocation Funds (DAU) on Local Expenditures in the Surabaya City Government - Jannah, Miftahul; Trisnaningsih, Sri (Jurnal Ekonomi Balance, 2022)
This study aims to examine and prove the effect of Regional Original Income (PAD), Special Allocation Funds (DAK), Revenue Sharing Funds (DBH), and General Allocation Funds (DAU) on Regional Expenditures in the Surabaya City Government. This study uses a quantitative method. The data used is in the form of secondary data, namely the 2011-2020 budget realization report taken from Badan Pengelolaan Keuangan dan Aset Daerah Kota Surabaya (BPKAD) and website (https://www.surabaya.go.id/). The sampling technique used is a saturated sample. The data analysis technique used was classical assumption test analysis and multiple linear regression analysis. Hypothesis testing using multiple linear regression analysis using the SPSS program with a significance level of 0,05. The results of the partial test show that the PAD variable has a significant effect on Regional Expenditures. While the variables of the DAK, DBH and DAU partially have no effect on Regional Expenditures. In the F (simultaneous) test, the variables of PAD, DAK, DBH and DAU simultaneously affect Regional Expenditures.